Tom est mort/Mot est mort – l'impossibilité du langage dans le roman de Marie Darrieussecq - Kotowska, Katarzyna (Quêtes littéraires, 2011)
An emptiness after one’s child death seems to be impossible to describe. In her novel Tom is dead, Marie Darrieussecq explores mother’s forbidden thoughts. She reconstructs her grieving process ten years after an accidental death of her four years old son. She starts to write a journal to finally deal with her trauma. Darrieussecq challenges the taboo or writing about things that words are almost impossible to express. The significant thing is that the boy’s name “Tom”, is the anagram of “mot” which stands for “a word” in French. For that reason the death of Tom becomes the death of word. The analysis of the novel in the optic of psychoanalysis results in interesting conclusions, just likewise Marie Darrieussecq’s study in meta-literary context.